PENGARUH KUALITAS PELAYANAN, KEWAJIBAN MORAL DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK HOTEL - Sentanu, I Nyoman Wirya; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
Local taxes are taxes that implementation is carried out by local governments. Local tax revenue is used to finance regional development. Local tax revenue Badung one of which is sourced from the hotel tax. This study aims to determine whether the quality of service, moral obligation and tax penalties affect taxpayer compliance hotels in Badung Regional Revenue Office. This research was conducted at the Department of Revenue Badung. The number of samples studied were 94 taxpayers hotels. The sampling method using a technique that is based on coincidence and accidental data collection is done through questionnaires. The analysis technique used is multiple linear regression analysis. This study obtain the results of service quality has positive influence on tax compliance hotel, a moral obligation positive effect on tax compliance hotels, and tax penalties negatively affect tax compliance hotel.
Keywords: Quality of Service, Moral Obligation Taxation, and Sanctions Taxpayer Compliance